PENINGKATAN LITERASI MEMBACA MELALUI MODEL PROBLEM SOLVING BERBANTUAN MAGIC SPIN BOARD - Ernida Ainun Nikmah; Sri Utaminingsih; Siti Masfuah (Universitas Muria Kudus, 2021)
The research aims to determine the increase in reading literacy through a problem solving learning model assisted by magic spin board media. The research method used is classroom action research with the subject of 20 students from SD 2 Rejosari grade fourth. The study was conducted in two cycles and each cycle consisted of two meetings held on the theme of the senven cultural diversity of my country. The research stages consisted of planning, implementing the action, observing and reflecting. The results of the study showed that the average percentage of cycle 1 was 69.88% and cycle 2 was 80.33% which indicated an increase in each cycle. The research shows that there is an increase in reading literacy with the use of problem solving learning models assisted by magic spin board media.